Disaster risk reduction for frequent occurrence of cyclone and floods: a case of Jagatsinghpur, Odisha - Mandal, Kasturi (SPA Bhopal, 2018)
Floods and cyclones are regular occurrences in coastal regions of Odisha. Despite having a long history of disasters and after much efforts from Odisha State Disaster Management Authority and several NGOs, the ground reality is something different and there lies a gap which yearns to be mended at the earliest. Jagatsinghpur is one of the coastal districts which gets affected by floods and cyclones regularly but is overshadowed by the adjoining Puri and Kendrapara districts due to their attractive tourist locations. The reality is that the study area comprises of critical eco-sensitive zone and also it falls in the direct path of cyclonic storms over Bay of Bengal. The aim is to suggest interventions which might bring down the vulnerability level of the study area. For the same, it is important to find out how vulnerable the coastline of Jagatsinghpur is, which is done by applying the Coastal Vulnerability Index method on basis of few identified parameters. The probable causes and impacts of frequent disasters on the study area from a socio-economic and environmental viewpoint is also a determining factor in the interventions which is analysed through primary surveys, stakeholder interviews and accounts of previous disasters and documents obtained from the secondary sources. The coast of Jagatsinghpur is not a stable coast and is found to be undergoing fast rates of erosion as well as accretion. Human-environment interaction, especially disaster inducing human interaction needs to be considered in planning as observed from the study. Attention should be given towards both the proactive and reactive approaches, strong stakeholder participation, community-based disaster reducing techniques, private-public partnership in managing the disasters, as well as alternative methods of land use planning and strengthening of infrastructural facilities which will go a long way in controlling the vulnerability levels before, during and after the disaster, and also enhancing the adaptive capacity and coping mechanisms amongst the inhabitants of the coastal areas of the district.
Keywords: MEP (Master of Environmental Planning); Floods